2021
DOI: 10.1021/acsanm.1c00373
|View full text |Cite
|
Sign up to set email alerts
|

Crack-Free Conjugated PbS Quantum Dot–Hole Transport Layers for Solar Cells

Abstract: Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…We performed SCAPS simulation to determine the active QD layer's optimum electron and hole mobilities for PCE maximization. [50,51] The PCE of solar cells as a function of electron mobility (within the range 10 À4 to 1 cm 2 V À1 s À1 ) is shown in Figure 5b, determined for different hole mobilities. The SCAPS parameters used for the simulation study are shown in Table S2, Supporting Information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed SCAPS simulation to determine the active QD layer's optimum electron and hole mobilities for PCE maximization. [50,51] The PCE of solar cells as a function of electron mobility (within the range 10 À4 to 1 cm 2 V À1 s À1 ) is shown in Figure 5b, determined for different hole mobilities. The SCAPS parameters used for the simulation study are shown in Table S2, Supporting Information.…”
Section: Discussionmentioning
confidence: 99%
“…This prompts us to determine the electron and hole mobility of the n-PbS and p-PbS layer using the space charge limited conduction (SCLC) method (Figure S11 a&b, Supporting Information). [10,51] The electron mobility of n-PbS (1.06 Â 10 À3 cm 2 V À1 s À1 ) is almost nine times higher than p-PbS (1.22 Â 10 À4 cm 2 V À1 s À1 ). However, the hole mobility of n-PbS (6.85 Â 10 À4 cm 2 V À1 s À1 ) is four times lower than p-PbS (2.63 Â 10 À3 cm 2 V À1 s À1 ).…”
Section: Discussionmentioning
confidence: 99%
“…73,92,93 Nevertheless, EDT ligands have introduced some negative issues, e.g., notorious pungent odor, pinhole stemming from their strong reactivity, passivation destruction of the active layer, and tedious solid-state ligand exchange (SSLE). [94][95][96] In this regard, Sargent's group has contributed considerably to address this challenge. Their recent work replaced conventional EDT ligands with nontoxic malonic acid (MA), which has nearly no impact on the bottom layer, due to the moderate reactivity (Fig.…”
Section: Lead Chalcogenide Qd Passivationmentioning
confidence: 99%
“…Furthermore, due to the strong reactivity of EDT in removing the initial long-chain oleic acid (OA) from the surface of PbS-CQDs, film volume contraction can lead to cracking and the formation of more interface defects. 31,32 Therefore, the PbS-EDT HTL leads to significant V OC losses in PbS-CQDSCs, underscoring the urgent need to search for alternative ligand exchange strategies.…”
Section: ■ Introductionmentioning
confidence: 99%